Study of functional outcome of surgical management of proximal humerus fracture by various modalities: a two-year study at a tertiary care hospital - Vijayanand, Addanki; Jayasomeswar, Narreddy (International Journal of Research in Orthopaedics, 2020)
Background: Proximal humerus fractures account for nearly 6-10% and are on a rise. The management of this is controversial and is challenging task. There is a significant heterogeneity among the studies in describing the best surgical procedure in proximal humerus fracture. The objective of the study is to assess and compare the functional outcome with different modalities in fixation of proximal humerus shaft fractures. Methods: A two-year prospective study was conducted after getting ethical approval at Narayana Medical College on cases admitted with proximal humerus fractures as per the inclusion criteria based on Neer’s classification. Radiological evaluation was done, and surgery was performed. Postoperative follow-up was done at 1st, 4th, 8th and 14th week and outcome were evaluated for each case based on Neer’s shoulder score. Results: 30 cases were included with a mean age of 48.2 years. Road traffic injury was common cause of fracture. Of the total 30 cases, 23 cases had excellent results, 4 cases were satisfactory, 2 cases were unsatisfactory, and one case had a failure. The mean scores observed on Neer’s score was pain (33.5 units), Function (23.5 units), range of motion (16.55 units) and anatomy (6.9 units). Conclusions: Clinical evaluation, obtaining proper radiological views, age of the patient and activity holds the key for realistic approach and surgical management of complex humerus fractures. Proper patient selection and thorough knowledge of the anatomy and biomechanical principles are the pre-requisites for a successful surgery and good functional outcome.